ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸šå¦ç”Ÿå¯¹æ±‰è¯å½¢å®¹è¯é‡å çš„æŽŒæ¡æƒ…å†µåˆ†æž - Putri, Anggreani Aprilla; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn terms of learning Mandarin, there are concrete words and abstract words. In conrete words, there is one type of word that its sentence states modification function which is adjective. Reduplication adjective is important and a difficulty in learning. The Mandarin language programme students batch 2016 in Faculty of Teacher Education and Education Science Tanjungpura University frequently make mistakes in the application of reduplication adjective, for example in reduplication adjective type AA, AABB, ABAB, or Aé‡ŒAB.To analyse the mastery and difficulty level of the reduplication adjective of the Mandarin language programme students batch 2016 in Faculty of Teacher Education and Education Science Tanjungpura University, the writer used research test method to collect the data. The results of this paper shows there is a type of reduplication adjective that reaches 91%, which is type Aé‡ŒAB, meaning the specific type is not yet mastered. As a Mandarin language teacher, the writer hopes that this research can be a reference to help the students that learns Mandarin as their second language.Key words: reduplication adjective Mandarin language, reduplication adjective type, mastery analysis